1999
DOI: 10.1055/s-2008-1053379
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular Decompression as Treatment of Trigeminal Neuralgia in the Elderly Patient

Abstract: Elderly patients with idiopathic trigeminal neuralgia are commonly referred to percutaneous treatment if medical therapy has failed. Due to elaborated microsurgical techniques and perioperative care, minimal invasive neurosurgical operations like microvascular decompression (MVD) can be offered increasingly to elderly patients. We operated upon 8 elderly patients (median 70.5 years) suffering from trigeminal neuralgia using MVD in a one-year period (1995). Seven patients were free of pain at release. At a two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Several papers have concluded that MVD for patients over 65 has outcomes were similar to younger patients without an increase in the risk of serious morbidity or mortality. [41][42][43] Thus, MVD appears to be safe and effective even for older patients with trigeminal neuralgia if their general medical condition is stable and the aim of treatment is complete pain relief without medications.…”
Section: Discussionmentioning
confidence: 99%
“…Several papers have concluded that MVD for patients over 65 has outcomes were similar to younger patients without an increase in the risk of serious morbidity or mortality. [41][42][43] Thus, MVD appears to be safe and effective even for older patients with trigeminal neuralgia if their general medical condition is stable and the aim of treatment is complete pain relief without medications.…”
Section: Discussionmentioning
confidence: 99%
“…3,22,32 As the world's population ages, the safety of MVD in older persons has become a topic of increased interest. 2,8,9,12,13,25,27,29,30 To date, the safety of MVD in older patients has been examined through several small case series, which were * CHF = congestive heart failure. …”
Section: Discussionmentioning
confidence: 99%
“…As the incidence of TN increases with age, 17 the safety of MVD in the elderly population represents an important clinical question for treating physicians. Several small studies, 2,8,9,12,13,25,27,30 including a recent prospective analysis, 29 have suggested that the efficacy and safety of MVD in elderly patients are comparable with those in younger patients. Unfortunately these studies are limited by small sample sizes.…”
mentioning
confidence: 99%
“…The complication rates appear to be high compared with the results of previously published papers 27,32,33 ; 20% of the patients developed mild, and 10% severe complications. In only one patient the neurologic deficit persisted, whereas the other patients experienced only transient deficits.…”
Section: Safety Of Microvascular Decompression In Elderly Patientsmentioning
confidence: 58%
“…Because MVD is the first-line of treatment, and the world population is aging, increasing interest has been paid to evaluating the safety and efficacy of MVD in older patients. [24][25][26][27][28][29] MVD treatment in elderly patients has been examined in several small case series summarized in a meta-analysis by Sekula and colleagues 30 and a recent meta-analysis published by Rughani et al 31 Both meta-analyses independently reported that the efficacy of MVD was not statistically significantly different between younger and older patients. The authors established an age cut-off of 65 years because the in-hospital mortality rate rises, as does the risk of cardiac, pulmonary, thromboembolic, and cerebrovascular complications, in elderly patients.…”
Section: Efficacy Of Microvascular Decompression In Elderly Patientsmentioning
confidence: 99%